The dentin organic matrix – limitations of restorative dentistry hidden on the nanometer scale - Bertassoni, Luiz E. (Elsevier, 2012)
The prevention and treatment of dental caries are major challenges occurring in dentistry. The foundations for modern management of this dental disease, estimated to affect 90% of adults in Western countries, rest upon the dependence of ultrafine interactions between synthetic polymeric biomaterials and nanostructured supramolecular assemblies that compose the tooth organic substrate. Research has shown, however, that this interaction imposes less than desirable long-term prospects for current resin-based dental restorations. Here we review progress in the identification of the nanostructural organization of the organic matrix of dentin, the largest component of the tooth structure, and highlight aspects relevant to understating the interaction of restorative biomaterials with the dentin substrate. We offer novel insights into the influence of the hierarchically assembled supramolecular structure of dentin collagen fibrils and their structural dependence on water molecules. Secondly, we review recent evidence for the participation of proteoglycans in composing the dentin organic network. Finally, we discuss the relation of these complexly assembled nanostructures with the protease degradative processes driving the low durability of current resin-based dental restorations. We argue in favour of the structural limitations that these complexly organized and inherently hydrated organic structures may impose on the clinical prospects of current hydrophobic and hydrolyzable dental polymers that establish ultrafine contact with the tooth substrate.